Analysis of Planetary Gear of Toyota Rush AT 2012 - Adam Fathlevi; Rudi Suhradi Rachmat; Azhari Sastranegara (President University, 2020)
Gear is one of the most important part of power transmission system in a vehicle, and as the time goes by there possibly some failure happened on the gears. However, there is no information provided by car manufacturer regarding the life and the material of the gears. This report presents the analysis of the planetary gear used in Toyota Rush AT year made of 2012. The objectives of the research are: to study the planetary gear mechanism and how it works; to analyze the force and stress acting on the gears; and to select a suitable gear material that can withstand against the loads that happen on the gear. The research methodology is started with finding the gear dimension and gear ratio. The force acting on gear is calculated based on the torque and rotation speed provided in car specification. Then the selection material is carried out based on the amount of stress applied on the gear teeth that were calculated using AGMA standard formulation. Finally, the fatigue life prediction of the gears is calculated based on the previous stress acting on the gears. The calculation result suggested AISI 1050 steel as the selected gear material that can carry the bending stress of 476 MPa and categorized as low to high fatigue cycle.